1988
DOI: 10.1055/s-2006-962441
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic Principles ofPrunella vulgaris, Psychotria serpens, andHyptis capitata: Ursolic Acid and Related Derivatives1

Abstract: Bioassay-directed fractionation of the cytotoxic antileukemic extracts of Prunella vulgaris, Psychotria serpens, and Hyptis capitata has led to the isolation of ursolic acid as one of the active principles. Ursolic acid showed significant cytotoxicity in the lymphocytic leukemia cells P-388 and L-1210 as well as the human lung carcinoma cell A-549. It also demonstrated marginal cytotoxicity in the KB and the human colon (HCT-8) and mammary (MCF-7) tumor cells. Esterification of the hydroxyl group at C-3 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
2
5

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(85 citation statements)
references
References 5 publications
2
76
2
5
Order By: Relevance
“…Zouhiri et al (2000) found that the existence of carboxyl group at C-7 of styrylquinolines is important in biological activity and the replacement with carbomethoxy group at C-7 position would cause reduction or complete loss of activity. Lee et al (1988), also discovered that esterification of carboxyl group at C-17 of ursolic acid would lead to decrease in toxicity. Hata et al (2002) reported that the carboxylic group of betulinic acid at C-17 position is important for the cancer cell apoptosis, where the existence of carboxylic group enhances its potency.…”
Section: Cytotoxicity Of Compounds 1 and 2 Towards Various Cancer Celmentioning
confidence: 99%
“…Zouhiri et al (2000) found that the existence of carboxyl group at C-7 of styrylquinolines is important in biological activity and the replacement with carbomethoxy group at C-7 position would cause reduction or complete loss of activity. Lee et al (1988), also discovered that esterification of carboxyl group at C-17 of ursolic acid would lead to decrease in toxicity. Hata et al (2002) reported that the carboxylic group of betulinic acid at C-17 position is important for the cancer cell apoptosis, where the existence of carboxylic group enhances its potency.…”
Section: Cytotoxicity Of Compounds 1 and 2 Towards Various Cancer Celmentioning
confidence: 99%
“…Experimental research on the apoptosis of cancer cells in vitro indicated that P. vulgaris could induce the apoptosis of SGC-7910 cancer cells and block the cell cycle between the G1 and G2 [78]. The experiment on the anti-tumor in vivo also showed that ursolic acid and its derivatives in P. vulgaris might show remarkable cytotoxic activity on P388, L1210 and human lung tumor cells A-549 [79]. By injecting rabbits with P. vulgaris with hydrothorax, Xu observed that the pleural surfaces of the experimental rabbits were rough, reddish and congested with adhesive tendency, which was verified by microscopic examination showing the obvious fibrotic thickening between the splanchnic layer pleurae in the thoracic cavity of the experimental rabbits adhered by large amount of lymphocytes.…”
Section: Antineoplastic Activitiesmentioning
confidence: 99%
“…238-240°C; Lee et al, 1988). Os dados espectrais que permitiram a identificação do ácido ursólico foram obtidos por espectrometrias no infravermelho (IV), de massas com impacto eletrônico (EMIE), ressonância magnética nuclear de hidrogênio (RMN …”
Section: Identificação Do áCido Ursólicounclassified
“…Análise espectrométrica (IV, EM, RMN 1 H e RMN 13 C) e comparação com dados da literatura (LEE et al, 1988) O ácido ursólico foi submetido aos testes biológicos, em diferentes concentrações (Tabela 10). Os resultados mostraram a eliminação total do Trypanossoma cruzi (cepa Y), nas concentrações de 1,6; 0,8 e 0,4mg/ml, e, na concentração de 0,2mg/ml, este composto foi parcialmente ativo.…”
Section: Identificação Do áCido Ursólico E Avaliação Da Sua Atividadeunclassified